Measurements of the branching fractions for B(s)→D(s)πππ and Λ0b→Λ+cπππ - Aaij, Roel; Bachmann, Sebastian; Bien, Alexander; Deissenroth, Marc; Eisele, Franz; Färber, Christian; Hansmann-Menzemer, Stephanie; Holubyev, Kostya; Jäger, Andreas; Kreplin, Katharina; Krocker, Georg Alexander; Linn, Christian; et al. (Physical review. D, Particles, fields, gravitation, and cosmology, 2011)
Branching fractions of the decays Hb→Hcπ−π+π− relative to Hb→Hcπ− are presented, where Hb (Hc) represents ¯¯¯B0 (D+), B− (D0), ¯¯¯B0s (D+s), and Λ0b (Λ+c). The measurements are performed with the LHCb detector using 35 pb−1 of data collected at √s=7 TeV. The ratios of branching fractions are measured to be [B(¯¯¯B0→D+π−π+π−)]/[B(¯¯¯B0→D+π−)]=2.38±0.11±0.21, [B(B−→D0π−π+π−)]/[B(B−→D0π−)]=1.27±0.06±0.11, [B(¯¯¯B0s→D+sπ−π+π−)]/[B(¯¯¯B0s→D+sπ−)]=2.01±0.37±0.20, [B(Λ0b→Λ+cπ−π+π−)]/[B(Λ0b→Λ+cπ−)]=1.43±0.16±0.13 We also report measurements of partial decay rates of these decays to excited charm hadrons. These results are of comparable or higher precision than existing measurements.
*The LHCb Collaboration: R. Aaij, S. Bachmann, A. Bien, M. Deissenroth, F. Eisele, C. Färber, S. Hansmann-Menzemer, K. Holubyev, A. Jaeger, K. Kreplin, G. Krocker, C. Linn, J. Marks, M. Meissner, P. Seyfert, S. Stahl, U. Uwer, S. Wandernoth, D. Wiedner, A. Zhelezov [und 548 weitere Personen]
Im Titel ist der Ausdruck "(s)" sowie die Buchstaben b und c tiefgestellt
Im Titel ist die Zahl 0 und das Pluszeichen hochgestellt
Gesehen am 15.02.2022